PERANCANGAN SISTEM INFORMASIAKADEMIK BERBASIS WEB PADA SMP KARTIKA VIII-1 JAKARTA - Safira Sistya Cahyani (2022)
As an educational institution, schools are required to keep up with the times in order to improve the quality of education. Utilization of information technology at SMP Kartika VIII-1 Jakarta is considered not to have been fully realized, because there is still data processing that is done manually and not yet computerized. For example, in processing student data and paying tuition fees, it is still handwritten so that it is prone to writing errors, duplication of records, and the process of searching for student tuition payment history is quite time consuming. In addition, the delivery of academic information to parents is still not easily accessible. This study uses the Waterfall method and PIECES analysis. The purpose of this study is to build a web-based academic information system application at SMP Kartika VIII-1 Jakarta to function as a management of school academic data and as a medium for delivering academic information to students and parents of students in controlling the development of their children at school. Results The designed application features activity announcements, student tuition payment data management, teacher data, student data, lesson schedules, attendance, assessments, final reports of academic data, as well as notifications to parents via whatsapp messages.